Pathological Findings Associated With SARS-CoV-2 on Postmortem Core Biopsies: Correlation With Clinical Presentation and Disease Course - Ramos-Rincon, Jose-Manuel; Herrera-García, Cristian; Silva-Ortega, Sandra; Portilla-Tamarit, Julia; Alenda, Cristina; Jaime-Sanchez, Francisco-Angel; Arenas-Jiménez, Juan; Fornés-Riera, Francisca-Eugenia; Scholz, Alexander; Escribano, Isabel; Pedrero-Castillo, Víctor; Muñoz-Miguelsanz, Carlos; et al. (Frontiers in Medicine, 2022)
Background Autopsies can shed light on the pathogenesis of new and emerging diseases. Aim To describe needle core necropsy findings of the lung, heart, and liver in decedents with COVID-19. Material Cross-sectional study of needle core necropsies in patients who died with virologically confirmed COVID-19. Histopathological analyses were performed, and clinical data and patient course evaluated. Results Chest core necropsies were performed in 71 decedents with a median age of 81 years (range 52–97); 47 (65.3%) were men. The median interval from symptoms onset to death was 17.5 days (range 1–84). Samples of lung (n = 62, 87.3%), heart (n = 48, 67.6%) and liver (n = 39, 54.9%) were obtained. Fifty-one lung samples (82.3%) were abnormal: 19 (30.6%) showed proliferative diffuse alveolar damage (DAD), 12 (19.4%) presented exudative DAD, and 10 (16.1%) exhibited proliferative plus exudative DAD. Of the 46 lung samples tested for SARS-CoV-19 by RT-PCR, 39 (84.8%) were positive. DAD was associated with premortem values of lactate dehydrogenase of 400 U/L or higher [adjusted odds ratio (AOR) 21.73; 95% confidence interval (CI) 3.22–146] and treatment with tocilizumab (AOR 6.91; 95% CI 1.14–41.7). Proliferative DAD was associated with an onset-to-death interval of over 15 days (AOR 7.85, 95% CI 1.29–47.80). Twenty-three of the 48 (47.9%) heart samples were abnormal: all showed fiber hypertrophy, while 9 (18.8%) presented fibrosis. Of the liver samples, 29/39 (74.4%) were abnormal, due to steatosis (n = 12, 30.8%), cholestasis (n = 6, 15.4%) and lobular central necrosis (n = 5, 12.8%). Conclusion Proliferative DAD was the main finding on lung core needle necropsy in people who died from COVID-19; this finding was related to a longer disease course. Changes in the liver and heart were common.